If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 19 + -3m = -15 + 4m Reorder the terms: 19 + 5m + -3m = -15 + 4m Combine like terms: 5m + -3m = 2m 19 + 2m = -15 + 4m Solving 19 + 2m = -15 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 19 + 2m + -4m = -15 + 4m + -4m Combine like terms: 2m + -4m = -2m 19 + -2m = -15 + 4m + -4m Combine like terms: 4m + -4m = 0 19 + -2m = -15 + 0 19 + -2m = -15 Add '-19' to each side of the equation. 19 + -19 + -2m = -15 + -19 Combine like terms: 19 + -19 = 0 0 + -2m = -15 + -19 -2m = -15 + -19 Combine like terms: -15 + -19 = -34 -2m = -34 Divide each side by '-2'. m = 17 Simplifying m = 17
| 8+5x=9+4x | | 3m^2/9 | | -4v-4=-6v-20 | | 3c+10=2c-3 | | 3x-60=21 | | x^-3/4=.037 | | w-7=9+5-2w | | -4y+1=1-6y-10 | | 3/8x-1/2=21/8 | | s(s/3/5)=-3/7 | | -24=5x-8x | | -6p-9=3p | | 2b+1=18 | | -7+4z=2z+7 | | y-2=-7/8(x-8) | | -7+4f=2z+7 | | -9-u=-4u | | -14+34=6x-56 | | 6x+12=-6x-17 | | Y=-3*(3*3)-1 | | 6x+12=6x-17 | | -3+7f=8f+4 | | -13+6y= | | -csc(3.14/4) | | 2sec^2=0 | | 4x+15=-9x-17 | | Y=-3*(-3*-3)-1 | | 2x-30=5x-10 | | 4(x+4)=4(x+9) | | tan^4x-5tan^2x+4=0 | | 10x+15=6-2x+3 | | 40x+12(2x)=544 |